Pengaruh Kemampuan Pemecahan Masalah Matematis Terhadap Kemampuan Berpikir Kritis Matematis Peserta Didik - Anggreini, Ratih Dwi; Bharata, Haninda; Noer, Sri Hastuti (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
Problem solving skills and mathematical critical thinking must be possessed by students when learning mathematics. This study aims to determine the effect of problem solving ability with mathematical critical thinking. This study uses a correlational design (Correlational Design). Data collection techniques in the form of mathematical problem solving tests and mathematical critical thinking tests. The sample in this study was 56 students of class VIII SMP Negeri 2 Bandar Lampung in the even semester of the 2021/2022 academic year. The research instrument used is a mathematical problem solving test and a mathematical critical thinking test instrument. The data analysis technique used is Simple Linear Regression analysis. Based on the results of Simple Linear Regression analysis, it was concluded that there was an effect of mathematical critical thinking skills on students' mathematical problem solving abilities. The influence of mathematical critical thinking skills on mathematical problem solving abilities is 27%.